2022
DOI: 10.1002/app.52207
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐based fatigue criterion for rubber damage under multimode loadings

Abstract: An accurate prediction of the fatigue life of a rubber product is based on a criterion. Since strain can be measured directly in rubber components during a test, it would help design engineers improve product performance effectively if the strain‐based damage criteria can achieve high accuracy. Hence, the experimental data on the AE42 and AE2 specimens were utilized to test the suitability of the proposed damage criterion for rubber materials. The criterion includes three principal components determined by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It is observed that these results agree very well with experimental data. 18 The safety zone is remarkably reduced as the reliability values increase.…”
Section: Reliability Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that these results agree very well with experimental data. 18 The safety zone is remarkably reduced as the reliability values increase.…”
Section: Reliability Computationmentioning
confidence: 99%
“…Shanguann and Coworkers, 4 Belkhiria et al, 7 Zarrin-Ghalami and Fatemi 8,19 and Luo et al 17,18 employed strain-based fatigue criteria to assess fatigue damage. The Researchers in 4 and 7 found out that Green-Lagrange was the most appropriate parameter to evaluate fatigue time of rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (6) indicates that accurate estimation of parameters in the log-normal distribution model is the key to calculate the fatigue reliability of NR components. Based on the test results, the maximum likelihood estimation method is used to determine the parameters.…”
Section: P-s -N Curve Based On the Logarithmic Strain Amplitudementioning
confidence: 99%
“…5 Establishing a rubber fatigue life prediction model (also called the S-N curve) is an effective method to obtain the fatigue life of rubber isolators. 6 Unlike the mature and highly-developed fatigue theory of metal materials, the fatigue life theory of NR components is still developing. 5 The behavior of NR materials is complex owing to their high deformability, quasi-incompressibility, and stress softening.…”
Section: Introductionmentioning
confidence: 99%
“…• Strain-based fatigue criteria: Shanguann and coworkers [2], Belkhiria et al [4], Wang et al [7], Zarrin-Ghalami and Fatemi [8] and Luo et al [9,10].…”
Section: Introductionmentioning
confidence: 99%